2024
DOI: 10.3390/biom14020149
|View full text |Cite
|
Sign up to set email alerts
|

FLVCR1a Controls Cellular Cholesterol Levels through the Regulation of Heme Biosynthesis and Tricarboxylic Acid Cycle Flux in Endothelial Cells

Marta Manco,
Giorgia Ammirata,
Sara Petrillo
et al.

Abstract: Feline leukemia virus C receptor 1a (FLVCR1a), initially identified as a retroviral receptor and localized on the plasma membrane, has emerged as a crucial regulator of heme homeostasis. Functioning as a positive regulator of δ-aminolevulinic acid synthase 1 (ALAS1), the rate-limiting enzyme in the heme biosynthetic pathway, FLVCR1a influences TCA cycle cataplerosis, thus impacting TCA flux and interconnected metabolic pathways. This study reveals an unexplored link between FLVCR1a, heme synthesis, and cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(77 reference statements)
1
0
0
Order By: Relevance
“…Some of these findings align with our observations in endothelial cells [ 36 ]. Specifically, we found that FLVCR1a downmodulation in Sk-Hep1 cells, a widely acknowledged model for liver sinusoidal endothelial cells, and in breast-tumor-derived endothelial cells, both cultured in the presence of choline, enhances cholesterol synthesis.…”
Section: Flvcr1a Cargos: An Ongoing Debatesupporting
confidence: 92%
“…Some of these findings align with our observations in endothelial cells [ 36 ]. Specifically, we found that FLVCR1a downmodulation in Sk-Hep1 cells, a widely acknowledged model for liver sinusoidal endothelial cells, and in breast-tumor-derived endothelial cells, both cultured in the presence of choline, enhances cholesterol synthesis.…”
Section: Flvcr1a Cargos: An Ongoing Debatesupporting
confidence: 92%